DISPOSISI MATEMATIS SISWA DENGAN MENGGUNAKAN PEMBELAJARAN BERBASIS MASALAH - Astriani, Nurullita; Al Dhana, Muhammad Bayu (Program Studi Pendidikan Matematika, Fakultas Keguruan Dan Ilmu Pendidikan, Universitas Alwashliyah Medan, 2025)
Mathematical disposition is an affective ability that is important for students to have because through this ability, students' attitudes in facing problems in mathematics will be resolved properly. One of the efforts that can be done to improve mathematical disposition is by implementing problem-based learning. By providing contextual problems in mathematics learning, it can have an impact on interest, desire and awareness in the form of a strong tendency to think and behave towards mathematics and see the usefulness of mathematics. This research aims to analyze students' mathematical disposition using problem based learning.This type of research is Quasi-experimental research.This research was implemented at SMP Negeri 1 Pangkalan Susu. The population of this research was students of class IX. The sample used was students of class IX-1 as the experimental class and IX-2 as the control class. Based on the results of t-test used in the research, the t-count value was 3,508 and the t-table value for a value of 1.67. This means that the t-count value > t-table namely 3,508 > 1,67. The results of this research state that the mathematical disposition of students who use problem-based learning is better than the mathematical disposition of students who use conventional learning.